2018
DOI: 10.1016/j.agwat.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of soil water flow and heat transport in drip irrigated potato field with raised beds and full plastic-film mulch in a semiarid area

Abstract: Surface drip irrigation with full plastic-film mulch can increase crop yield and save water by regulating soil water and heat conditions for potato (Solanum tuberosum L.) production with raised beds in semiarid area where the rainfall is scarce and evaporation is high. For efficient use of plastic film mulch an understanding of the soil water flow and heat transport is needed. Here we use a model (HYRUS-2D) which is calibrated with field experiments to simulate soil water movement and heat transport. The field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…This might be related to larger hydraulic conductivity and lower saturated water content in deeper soil than in upper soil. Zhang et al (2018) obtained similar findings by simulating soil water distribution after irrigation in a semiarid area. Similarly, Cable and Huxman (2004) found that, in water-limited eco-systems, the effects of small rainfall events on soil water might persist for just a few hours.…”
Section: Discussionsupporting
confidence: 63%
“…This might be related to larger hydraulic conductivity and lower saturated water content in deeper soil than in upper soil. Zhang et al (2018) obtained similar findings by simulating soil water distribution after irrigation in a semiarid area. Similarly, Cable and Huxman (2004) found that, in water-limited eco-systems, the effects of small rainfall events on soil water might persist for just a few hours.…”
Section: Discussionsupporting
confidence: 63%
“…The study area was located at the Shiyanghe Experimental Station (N 37 • 52 , E 102 • 50 , altitude 1581 m), China Agricultural University, Wuwei, Gansu Province, on the border of the Tenger Desert with a typical continental temperate climate. The area has sufficient heat resources and limited water resources with mean annual temperature 8 • C, annual accumulated temperature (>0 • C) 3550 • C, annual sunshine duration 3000 h, annual precipitation 164 mm, pan evaporation 2000 mm, and groundwater table 5-30 m below ground surface [38]. The soil texture is sandy loam with mean soil bulk density 1.53 g/cm 3 at 0-1.0 m depth [11].…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…Among the available models (including SVAT, SHAW and HYDRUS) that can simulate the transport of water, heat and solute in variable-saturated porous media, we use the HYDRUS model in this work [27]. The geometric dimensions of ridges and furrows can be considered explicitly in HYDRUS-2D, whose effectiveness and accuracy for two-dimensional soil water and heat transport simulation have been verified by many scholars [28][29][30][31]. Most previous studies considered a no-flux boundary under film mulched areas [30,31], but the variable-flux boundary has been confirmed to be more practical [32] and was therefore adopted in this paper.…”
Section: Introductionmentioning
confidence: 99%